2018
DOI: 10.9734/cjast/2018/45224
|View full text |Cite
|
Sign up to set email alerts
|

Elephant Grass (Pennisetum purpureum): A Potential Source of Biomass for Power Generation in Ghana

Abstract: The Government of Ghana has introduced into its energy mix many thermal generation plants, which utilize natural gas and light crude oil to augment the electric power need of the country. However, these come with high fueling cost and frequent interruption in the supply chain. One area which has not been explored is the use of biomass for electrical power generation. Pennisetum purpureum K. Schumach grows in the wild as grass in the dry semideciduous forest zone and the distributional range covers an area of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Thermal methods are represented by combustion, pyrolysis and gasification, and hydrothermal methods [35][36][37][38]. Thermal or electrical energy is the primary product of BWW combustion; ash (10-20% by mass) is formed as a waste [39].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal methods are represented by combustion, pyrolysis and gasification, and hydrothermal methods [35][36][37][38]. Thermal or electrical energy is the primary product of BWW combustion; ash (10-20% by mass) is formed as a waste [39].…”
Section: Introductionmentioning
confidence: 99%
“…In livestock farming Mott grass is responsible for the production of good quality forage and also recommended for silage. According to research carried out in 2018, Brazil only generated 30-40 metric tons of its biomass per hectare under home condition while other areas produced 50-60 MT in five months using rectilinear growth rate (Danquah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, several studies have shown that there is a great potential for energy generation from waste produced in the country (Duku et al , 2011a, Ofori-Boateng, 2013; Mohammed et al , 2013; Kemausuor et al , 2014; Ulrike et al , 2014; Gyamfi et al , 2015; Danquah et al , 2018; Akolgo et al , 2018; Acheampong et al , 2019; Amo-Asamoah et al , 2020). Notwithstanding these potentials, there is yet no commercial facility or plant for waste-to-energy generation in the country (Bensah and Brew-Hammond, 2010).…”
Section: Introductionmentioning
confidence: 99%